HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PENCEGAHAN TERJADINYA KOMPLIKASI HIPERTENSI DI PUSKESMAS GONDOKUSUMAN II KOTA YOGYAKARTA - Theresia, Firmina; Istichomah, Istichomah; Titi Heryani, Retno (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2025)
Background: Untreated hypertension and poor management can cause complications, therefore you must comply with hypertension treatment. Treatment compliance is influenced by many factors, one of which is knowledge and behavior. Research Objective: To determine the relationship between level of knowledge and behavior to prevent hypertension complications in the Gondokusman II Community Health Center Work Area, Yogyakarta City. Research Method: This research is associative research, causal associative or causal relationships. The population in this study were all hypertensive patients registered at the Community Health Center in the Gondokusman II Community Health Center Working Area, Yogyakarta City in 2023 with a sample of 83 people. The sampling technique is quota sampling. The research instrument used a questionnaire. The data analysis technique uses the Somers'd test. Research Results: The level of knowledge of preventing hypertension complications was mostly good, as many as 52 people (62,7%). The preventive behavior carried out by patients as an effort to prevent hypertension complications was mostly good, as many as 49 people (59,0%). There was a relationship between the level of knowledge of hypertensive patients and the behavior to prevent the occurrence of hypertension complications in patients with a p value of 0,003. Conclusion: There is a relationship between the level of knowledge of hypertensive patients and the behavior of preventing hypertension complications in patients in the Gondokusuman II Health Center Working Area, Yogyakarta City.